KINETIKA ADSORPSI-REDUKSI ION Au(III) PADA ASAM HUMAT HASIL ISOLASI DARI TANAH GAMBUT RAWA PENING - Dian Prasasti; Sri Juari; Sri Sudiono (Universitas Ahmad Dahlan, 2013)
Isolation of peat soil humic acid and its application for adsorption reduction of Au(III) have been conducted. Humic acid was isolated from peat soil that was collected from Rawa Pening, Central Java. Isolation of humic acid from peat soil was based on conventional alkaline extraction method. Humic acid was extracted from peat soil with NaOH 0.1 M, then precipitated with 0.1 M HCl, and purified with 0.1 M HCl/0.3 M HF 1/1. The isolated humic acid was characterized by FTIR spectroscopy, then applied for adsorption and reduction process of Au (III).Adsorption kinetics on adsorption reduction process of Au (III) also were studied. The gold metal formed was confirmed by XRD diffractogram, and photo optical microscope. The adsorption rate constant (k) with Santosa kinetics model for humic acid is 0.0065 min-1.Peaks of gold particles in the difractogram are 2 = 38, 44 and 64.